Underground Environments, Worldviews, and Sustainable Stewardship - Reuben Grima (MDPI AG, 2021)
This paper examines an aspect of a value-based approach to underground built heritage (UBH). A key tool for the manager of any built heritage today is the mapping of its manifold values for different audiences, to inform their management strategy. This paper first reviews an important paradigm shift that has occurred in the humanities and in cultural heritage management, leading to the recognition of the centrality of the worldviews and lived experience of the different members that make up communities. Drawing on a selection of examples from the literature, it then demonstrates how many UBH sites across a wide spectrum of cultures acquired cosmological and cultic value and significance in a way that is qualitatively different to most built heritage sites above ground. The spectrum of challenges that this poses to the UBH site manager is then outlined by reviewing literature on a selection of UBH examples, from prehistoric archaeological sites to living religious sites. Some key guiding principles are proposed for the management of these different scenarios. Culturally sensitive management that respects the existing value systems of local communities is indispensable wherever such communities are present. Decision-makers need to be keenly aware of these value systems and need to recognize, empower, and complement existing traditional systems of stewardship.